2009
DOI: 10.1007/s00540-008-0700-9
|View full text |Cite
|
Sign up to set email alerts
|

Perineural morphine in patients with chronic ischemic lower extremity pain: efficacy and long-term results

Abstract: A peripherally administered bupivacaine plus morphine combination provided better and longer analgesia for ischemic pain compared to bupivacaine alone for the short term, but not for the long term. On the other hand, our results show that continuous popliteal treatment is an effective, safe, and comfortable modality for long-term use in the home setting for patients with intractable chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Consistent with the animal data, pain relief from local application of opioids has been reported in patients with chronic rheumatoid and osteoarthritis, ischemic pain, dental pain, pancreatitis, and postoperative visceral pain (Dionne et al, 2001; Duckett et al, 1997; Eisenach et al, 2003; Keskinbora et al, 2009; Likar et al, 2001; Modi et al, 2009; Rorarius et al, 1999). …”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with the animal data, pain relief from local application of opioids has been reported in patients with chronic rheumatoid and osteoarthritis, ischemic pain, dental pain, pancreatitis, and postoperative visceral pain (Dionne et al, 2001; Duckett et al, 1997; Eisenach et al, 2003; Keskinbora et al, 2009; Likar et al, 2001; Modi et al, 2009; Rorarius et al, 1999). …”
Section: Introductionsupporting
confidence: 78%
“…Accumulating studies provide a compelling rationale for targeting peripheral ORs as a novel treatment for various types of pain (Keskinbora et al, 2009). Peripheral application of DOR agonists produces potent anti-hyperalgesic effects under inflammatory and neuropathic pain conditions (Kabli et al, 2007; Pacheco et al, 2005; Shinoda et al, 2007; Stein et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Keskinbora et al recently examined the use of bupivacaine versus bupivacaine plus morphine administered via a popliteal catheter for patients with chronic lower extremity pain. The study included a short-term single bolus treatment phase where morphine was noted to prolong analgesia by approximately three hours compared to bupivacaine alone [ 28 ]. It should be noted, however, that the morphine group experienced significantly greater side effects (nausea and somnolence).…”
Section: Resultsmentioning
confidence: 99%
“…The evidence supporting the role of peripheral opioid receptors in suppressing pain and hyperalgesia has been accumulated for decades (Stein et al, 2003). Not only in preclinical studies (Garlicki et al, 2006;Nunez et al, 2007;Guan et al, 2008;Obara et al, 2009), but clinical studies in patients also demonstrated the effects of peripheral opioid in multiple pain conditions (Duckett et al, 1997;Rorarius et al, 1999;Dionne et al, 2001;Likar et al, 2001;Eisenach et al, 2003;Keskinbora and Aydinli, 2009). We previously demonstrated the role of peripheral opioid receptors in attenuating mechanical hypersensitivity (Nunez et al, 2007;Saloman et al, 2011;Auh and Ro, 2012).…”
Section: Discussionmentioning
confidence: 99%